Protecting Trade From Protectionism - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Protecting Trade From Protectionism," written by Walter B. Wriston for a speaking engagement in Brussels on 24 October 1977. The original speech is located in MS134.001.003.00021.